The entropy of the noncommutative acoustic black hole based on generalized uncertainty principle - M.A. Anacleto; F.A. Brito; E. Passos; W.P. Santos (Physics Letters B, 2014)
In this paper we investigate statistical entropy of a 3-dimensional rotating acoustic black hole based on generalized uncertainty principle. In our results we obtain an area entropy and a correction term associated with the noncommutative acoustic black hole when λ introduced in the generalized uncertainty principle takes a specific value. However, in this method, it is not needed to introduce the ultraviolet cut-off and divergences are eliminated. Moreover, the small mass approximation is not necessary in the original brick-wall model.